Genomic epidemiological analysis reveals new insights into the resurgence of Mycoplasma pneumoniae in China - Wang, Xue; Zheng, Dandan; Gong, Cheng; Luo, Ming; Li, Aihua; Duan, Xuecong; Wang, Chengcheng; Hu, Geng; Guan, Xuejiao; Yang, Fan; Huang, Fang; Chen, Lihong (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesAfter coronavirus disease 2019 pandemic restrictions, Mycoplasma pneumoniae (M. pneumoniae) re-surged widely across the world. This study aimed to determine the genomic epidemiological characteristics of resurging M. pneumoniae, which has dominated the respiratory infection outbreak in Beijing, China, since mid-September 2023.MethodsM. pneumoniae samples were collected from patients with acute respiratory-tract infections in Beijing in 2018–2023. A total of 160 M. pneumoniae genomes were sequenced via probe-capture-based approach. The genetic features of M. pneumoniae were characterized by multilocus sequence typing and comparative genomic analysis.ResultsIn total, 160 patients with M. pneumoniae infections were enrolled. ST3 (n = 93) and ST14 (n = 65) were the predominant sequence types. The macrolide-resistant mutation rate of ST3 was maintained at 100%, whereas that of ST14 increased rapidly. Comparative genomic analysis revealed 99% to > 99% similarity among the Beijing strains from 2023 when aligned to the reference M129 genome. The major variation occurs in the P1 gene. MAUVE indicated a lack of rearrangement, yet it included four subtype-specific insertions and non-conserved hsdS genes. The phylogenetic tree showed that strains from Asia and other world regions clustered into distinct clades, with significant evolutionary differences. Further genomic analyses identified some Asia-dominant genetic variations in genes associated with genome stability, pathogenesis, and drug resistance.ConclusionsThe 2023 outbreak of M. pneumoniae was not attributable to a novel variant but stemmed from the resurgence of the pre-existing strains. Our genomic epidemiological findings demonstrated that the endemic strains in different regions exhibit distinct genomic characteristics, associated with genomic stability.